Institutional Trust 2007 - telephone interviews - Holmberg, Sören; Weibull, Lennart; MedieAkademin; TNS Gallup (University of Gothenburg, 2014)
Since 1997, MedieAkademin has carried out an annual survey titled The Institutional Trust. The survey has focused on major social institutions, such as the parliament, big business, the daily press, and TV/radio, as well as some specific companies such as Sveriges Television, TV4, IKEA, Skandia, and Volvo. The number of institutions included has varied somewhat over the years. Some of the institutions and companies have been measured every year while others have been investigated more irregularly.

The survey was carried out by TNS Gallup and involved 250 individuals who were interviewed by telephone and 750 individuals randomly selected from TNS Gallup’s Online Panel who answered a web survey between October 15 and 29, 2007. The survey comprised 27 institutions/companies/media companies and political parties. The 2007 survey also included questions about morality in different groups of people and how it has changed over time, as well as what responsibilities large corporations have and to what extent they live up to these responsibilities.

Purpose:

To study the trust that Swedish people have in social institutions, political parties, media, brands/companies, and leaders.

MedieAkademins förtroendebarometer har genomförts årligen sedan 1997. Undersökningen har varje år dels avsett ett urval viktiga samhällsinstitutioner som exempelvis riksdagen, storföretagen, dagspressen och radio-TV, dels ett antal konkreta medier, bl.a Sveriges Television och TV4, och specifika företag, som t ex IKEA, Skandia och Volvo. Antalet bedömda institutioner har varierat något mellan enskilda år. Vissa av institutionerna/medierna/företagen har mätts varje år, andra har studerats mer oregelbundet.

Undersökningen 2007 omfattade 250 personer intervjuade via telefon och 750 personer slumpvis utvalda från TNS Gallups On Line Panel som besvarat en nätenkät. Studien genomfördes 15/10 - 29/10 2007. Undersökningarna har genomförts av TNS Gallup i Göteborg och innefattade 27 institutioner/företag/medier/partier. I 2007 års undersökning ingick även frågor om olika gruppers moral och hur den har förändrats liksom frågor om storföretagens ansvar och hur de lever upp till dem.

Syfte:

Studera svenska folkets förtroende till samhällsinstitutioner, politiska partier, medier, varumärken/företag och ledare.
Förtroendebarometer 2007 - telefonintervju
Keywords: mass media; massmedia; trust; förtroende; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; Media; Media; POLITICS; POLITIK; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper